Ecuador and the FTAA: Issues for reflection - Falconí Morales, Juan (2016)
The article analyses the current state of the Free Trade Area of the Americas (FTAA) negotiations. It is hold that Ecuador should take precautions due to its dollarization. According to the author, both public policies and microeconomic administration should be seen from a different perspective, one which could be capable of creating a special regime for the small countries. A Hemispheric Cooperation Program is also outlined. Since the FTAA could bring about some major risks to the Andean Region, the author emphasizes that a long-term strategy must be envisioned.